INTEGRATING DIGITAL STORYTELLING TO IMPROVE WRITING AND PRONUNCIATION IN ESL STUDENTS - Nigoraxon Mashrabova Muhammadzokir qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article explores the integration of digital storytelling (DST) as an innovative pedagogical tool aimed at enhancing writing and pronunciation skills in English as a Second Language (ESL) students. The study examines how DST facilitates language learning by fostering creativity, engagement, and active participation among ESL learners. The article further delves into the methodology, results, and effectiveness of digital storytelling in improving both writing and pronunciation skills.